Mutations in Efflux Pump Rv1258c (Tap) Cause Resistance to Pyrazinamide, Isoniazid, and Streptomycin in M. tuberculosis - Liu, Jiayun; Shi, Wanliang; Zhang, Shuo; Hao, Xiaoke; Maslov, Dmitry A.; Shur, Kirill V.; Bekker, Olga B.; Danilenko, Valery N.; Zhang, Ying (Frontiers in Microbiology, 2019)
Although drug resistance in M. tuberculosis is mainly caused by mutations in drug activating enzymes or drug targets, there is increasing interest in possible role of efflux in causing drug resistance. Previously, efflux genes are shown upregulated upon drug exposure or implicated in drug resistance in overexpression studies, but the role of mutations in efflux pumps identified in clinical isolates in causing drug resistance is unknown. Here we investigated the role of mutations in efflux pump Rv1258c (Tap) from clinical isolates in causing drug resistance in M. tuberculosis. We constructed point mutations V219A, S292L in Rv1258c in the chromosome of M. tuberculosis and the point mutations were confirmed by DNA sequencing. The susceptibility of the constructed M. tuberculosis Rv1258c mutants to different tuberculosis drugs was assessed using conventional drug susceptibility testing in 7H11 agar in the presence and absence of efflux pump inhibitor piperine. C14-labeled PZA uptake experiment was performed to demonstrate higher efflux activity in the M. tuberculosis Rv1258c mutants. Interestingly, the V219A, S292L point mutations caused clinically relevant drug resistance to pyrazinamide (PZA), isoniazid (INH), and streptomycin (SM), but not to other drugs in M. tuberculosis. While V219A point mutation conferred a low-level drug resistance, the S292L mutation caused a higher level of resistance. Efflux inhibitor piperine inhibited INH and PZA resistance in the S292L mutant but not in the V219A mutant. S292L mutant had higher efflux activity for pyrazinoic acid (the active form of PZA) than the parent strain. We conclude that point mutations in the efflux pump Rv1258c in clinical isolates can confer clinically relevant drug resistance including PZA resistance and could explain some previously unaccounted drug resistance in clinical strains. Future studies need to take efflux mutations into consideration for improved detection of drug resistance in M. tuberculosis and address their role in affecting treatment outcome in vivo.